Catalytically inactive Cas9 attenuates DNA end resection: A potential application for region-restricted random mutagenesis - Suchin Towa; Satoshi Okada; Takashi Ito (iScience)
Summary: Gene duplication followed by sequence diversification is a key driver of innovation in genome evolution. To mimic this process in genome engineering, a method for region-restricted mutagenesis is needed to selectively mutate one copy of a duplicated gene. Notably, regions flanking a double-strand break (DSB) become hypersensitive to mutagens due to end resection, which converts them into single-stranded DNA (ssDNA). Blocking end resection could, therefore, confine hypermutation to a limited region. To achieve this, we investigated a catalytically inactive variant of Streptococcus pyogenes Cas9 (dSpCas9) and demonstrated its ability to attenuate end resection in the budding yeast Saccharomyces cerevisiae using ssDNA-specific quantitative PCR, live-cell imaging, and Southern blot analysis. By leveraging the bisulfite sensitivity of ssDNA, we further validated the concept of DSB-coupled, dSpCas9-mediated region-restricted mutagenesis. We anticipate that dSpCas9-mediated modulation of end resection at induced DSB sites will have valuable applications in both genome engineering and mechanistic studies.